High-strength corrosion-resistant special 3D printing wire rod and preparation method thereof

By introducing crosslinking groups in polyetherimide and polyether ether ketone, and introducing fluorenyl groups on perfluorinated graphene and covalently connecting them with amino quartz fibers, the existing 3D printed wires are solved in strength, The lack of hardness and corrosion resistance has achieved higher performance 3D printed wires.

CN119391161APending Publication Date: 2025-02-07TUOQI NEW MATERIAL TECH (WUXI) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411356647.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing 3D printed wires cannot meet specific market demands in terms of strength, hardness and corrosion resistance.

Method used

The mechanical properties and thermal stability of the material are enhanced by introducing phenylacetylene crosslinking groups into polyetherimide and melt extrusion and granulation with polyether etherketone; at the same time, by perfluorinated graphene Fluorene groups are introduced on the surface and covalently linked to the aminolated chopped quartz fibers, improving the corrosion resistance and strength of the material.

Benefits of technology

It significantly improves the strength, corrosion resistance and thermal stability of 3D printed wires, meeting the market demand for higher performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of 3D printing wires, and particularly discloses a high-strength corrosion-resistant special 3D printing wire and a preparation method thereof. Comprising the following operation steps: S1, preparing modified fluorinated graphene: (1) reacting fluorinated graphene with N-methyl-2-pyrrolidone to obtain perfluorinated graphene; (2) reacting the perfluorinated graphene with bisphenol fluorene by taking potassium carbonate as a catalyst to obtain modified fluorinated graphene; s2, uniformly mixing polyether-ether-ketone, the modified polyether-ether-ketone, the modified fluorinated graphene and the modified composite material to obtain a premix, performing melt extrusion on the premix, and performing wire drawing and winding to obtain the 3D printing wire.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of 3D printing wires, and in particular to a high-strength, corrosion-resistant special 3D printing wire and a preparation method thereof. Background Art

[0002] In the existing technology, 3D printing technology of engineering plastics has been widely used in the fields of industry, aerospace, etc. As a special engineering plastic, polyetheretherketone has good corrosion resistance, excellent biocompatibility and high temperature resistance, which makes it widely used in the field of 3D printing. With the advancement and development of science and technology, the strength, hardness and corrosion resistance of 3D printing wires can no longer meet specific market requirements.

[0003] In summary, in order to solve the above problems, it is of great significance to prepare a high-strength and corrosion-resistant special 3D printing wire. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength, corrosion-resistant special 3D printing wire and a preparation method thereof to solve the problems raised in the above-mentioned background technology.

[0005] A method for preparing a high-strength, corrosion-resistant special 3D printing wire comprises the following steps:

[0006] S1: (1) Under nitrogen protection, 4,4'-diaminodiphenyl ether is dissolved in N,N-dimethylacetamide and stirred for 5-10 minutes, diphenyl diether dianhydride is added and reacted at room temperature for 12-14 hours, phenylacetylene tricarboxylic anhydride is added and the reaction is continued for 5-6.5 hours, triethylamine and acetic anhydride are added in sequence and reacted for 3-4 hours, and purified to obtain polyetherimide; (2) polyetherimide and polyetheretherketone are mixed evenly, melt-extruded and granulated to obtain modified polyetheretherketone.

[0007] S2: (1) adding fluorinated graphene to N-methyl-2-pyrrolidone, reacting at 55-65°C for 4-7 hours, cooling to room temperature, ultrasonically treating in an ice bath for 14-16 hours, purifying, and obtaining perfluorinated graphene; (2) adding perfluorinated graphene, bisphenol A and potassium carbonate to a mixed solution of cyclobutane sulfone and toluene, stirring at 135-145°C for 1-2 hours under nitrogen protection, heating to 160-175°C for reaction for 1.5-2.5 hours, cooling to room temperature, purifying, and drying to obtain modified fluorinated graphene.

[0008] S3: (1) adding fluorinated graphene to diphenyl ether for ultrasonic dispersion, adding sodium amide, introducing nitrogen, reacting at 160-165° C. for 12-13 hours, cooling to room temperature, quenching, and purifying to obtain amino fluorinated graphene; (2) placing short quartz fibers in H 2 SO4 The aqueous solution is stirred and ultrasonically treated for 5 to 7 minutes, placed at 55 to 65° C. for reaction for 45 to 65 minutes, cooled to room temperature, and amino-fluorinated graphene is added, stirred for 1 to 1.2 hours, the pH is adjusted to neutral, washed, and dried to obtain a modified composite material.

[0009] S4: uniformly mixing polyetheretherketone, modified polyetheretherketone, modified fluorinated graphene and modified composite material to obtain a premix, melt-extrude the premix, and draw and wind the premix to obtain a 3D printing filament.

[0010] More optimally, the raw materials of the premix include the following components: by weight, 62-75 parts of polyetheretherketone, 25-35 parts of modified polyetheretherketone, 3-5 parts of modified fluorinated graphene, and 15-20 parts of modified composite material.

[0011] More optimally, the raw materials of the polyetherimide include the following components: by weight, 8 to 10 parts of 4,4'-diaminodiphenyl ether, 18 to 22 parts of biphenyl diether dianhydride, 2 to 3 parts of phenylacetylene tricarboxylic anhydride, 12 to 14 parts of triethylamine, 12 to 14 parts of acetic anhydride, and 100 to 200 parts of N,N-dimethylacetamide; the polyetherimide accounts for 16 to 20 wt% of the polyetheretherketone; the process conditions of melt extrusion granulation are: the temperature of zone 1 is 320 to 325°C, the temperature of zone 2 is 345 to 350°C, the temperature of zone 3 is 362 to 365°C, the die temperature is 360°C, and the rotation speed is 27 to 35 r / min.

[0012] More optimally, the mass ratio of the fluorinated graphene to N-methyl-2-pyrrolidone is (0.005-0.01):1; the raw materials for the modified fluorinated graphene include the following components: by weight, 1-1.5 parts of perfluorinated graphene, 0.2-0.8 parts of bisphenol fluorene, 0.8-1.2 parts of potassium carbonate, 8-10 parts of cyclopentane sulfone, and 2-3 parts of toluene.

[0013] More optimally, the H 2 SO 4 The concentration of the aqueous solution is 0.023-0.037 wt %; the mass ratio of sodium amide to fluorinated graphene is (1-2):1; the aminated fluorinated graphene accounts for 0.2-0.4 wt % of the chopped quartz fibers.

[0014] The more optimized process conditions for the melt extrusion are: the temperature of zone 1 is 325-335°C, the temperature of zones 2 to 11 is 350-375°C, the die temperature is 378°C, and the main engine speed is 350-450r / min.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: polyetherimide has good tensile strength and wear resistance. In order to improve the stability and strength of polyetherimide and polyetheretherketone after blending, the present invention introduces phenylacetylene cross-linking groups into polyetheramide, and cross-links with multiple polyetheretherketones through melt extrusion granulation, thereby enhancing the mechanical properties and thermal stability of polyetheretherketone.

[0016] Compared with fluorinated graphene, perfluorinated graphene has better corrosion resistance, thermal stability and strength. In order to improve the dispersibility of perfluorinated graphene in polyetheretherketone, fluorene groups are introduced on its surface; the fluorene groups can not only improve the rigidity, but also increase the interaction force between it and the polyetheretherketone molecules, and effectively reduce the aggregation of perfluorinated graphene particles, improve its dispersibility in the polyetheretherketone matrix, and thus improve the corrosion resistance and strength of 3D printing filaments.

[0017] Chopped quartz fiber is a special fiber with excellent mechanical properties, chemical stability and thermal properties. The present invention adds chopped quartz fiber and fluorinated graphene as fillers into the matrix polyetheretherketone. In order to improve the dispersibility of the two in polyetheretherketone, the present invention introduces amino groups on the fluorinated graphene and introduces hydroxyl groups on its surface through acid / base etching treatment; the amino graphene oxide and the hydroxylated chopped quartz fiber are covalently connected to obtain a modified composite material, which can enhance the strength, corrosion resistance, high thermal conductivity and wear resistance of the material. Covalent connection can reduce the aggregation phenomenon between fluorinated graphene and chopped quartz fibers, make the interaction between them more uniform, and help improve their dispersibility in polyetheretherketone, thereby improving the performance of 3D printing materials.

[0018] The present invention uniformly mixes polyetheretherketone, modified polyetheretherketone, modified fluorinated graphene, and modified composite materials, and melts and extrudes them through different temperature zones, cools them, and reels them to obtain 3D printing wires. For the modified materials, modified polyetheretherketone, modified fluorinated graphene, and modified composite materials, by extruding them in different temperature zones, the dispersibility and fluidity of the modified materials can be improved, ensuring that the additives are fully dispersed in the matrix, thereby improving the performance of the 3D printing wires. DETAILED DESCRIPTION

[0019] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.

[0020] In the following specific embodiments, parts are by weight. In the present embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention include, without any special restrictions, exemplarily: the CAS number of 4,4'-diaminodiphenyl ether is 101-80-4, the CAS number of N,N-dimethylacetamide is 127-19-5, the CAS number of biphenyl diether dianhydride is 26177-82-2, the CAS number of phenylacetylene tricarboxylic anhydride is 1329658-14-1, the CAS number of triethylamine is 121-44-8, and the CAS number of ethyl The CAS number of acid anhydride is 114510-14-4, the product number of polyetheretherketone is HC7366, the product number of fluorinated graphene (fluorine content 53-60%) is M58045, the CAS number of N-methyl-2-pyrrolidone is 2687-44-7, the CAS number of bisphenol fluorene is 3236-71-3, the CAS number of potassium carbonate is 584-08-7, the CAS number of sodium amide is 7782-92-5, and the product number of chopped quartz fiber is 9603020.

[0021] Embodiment 1:

[0022] S1: (1) Under nitrogen protection, 8 parts of 4,4'-diaminodiphenyl ether are dissolved in 100 parts of N,N-dimethylacetamide and stirred for 5 minutes, 18 parts of biphenyl diether dianhydride are added and reacted at room temperature for 13 hours, 2 parts of phenylacetylene tricarboxylic anhydride are added and the reaction is continued for 5 hours, 12 parts of triethylamine and 12 parts of acetic anhydride are added in sequence and reacted for 4 hours, ethanol is washed 3 times, and dried to obtain polyetherimide; (2) polyetherimide and polyetheretherketone are mixed uniformly, placed in a single screw extruder for melt extrusion granulation, and the process conditions are: zone 1 temperature is 325°C, zone 2 temperature is 350°C, zone 3 temperature is 365°C, die head temperature is 360°C, and rotation speed is 30r / min; modified polyetheretherketone is obtained; wherein the polyetherimide accounts for 18wt% of the polyetheretherketone;

[0023] S2: (1) Weighing fluorinated graphene and N-methyl-2-pyrrolidone in a mass ratio of 0.008:1; adding fluorinated graphene to N-methyl-2-pyrrolidone, reacting at 60°C for 4.5 hours, cooling to room temperature, ultrasonically treating in an ice bath for 14 hours, centrifuging, and washing the precipitate with ethanol four times to obtain perfluorinated graphene; (2) adding 1 part of perfluorinated graphene, 0.2 parts of bisphenol A and 1 part of potassium carbonate to a mixed solution of 8 parts of cyclopentane sulfone and 2 parts of toluene, stirring at 142°C for 1.2 hours under nitrogen protection, heating to 160°C for 1.5 hours, cooling to room temperature, centrifuging, and washing the precipitate with ethanol four times to obtain modified fluorinated graphene;

[0024] S3: (1) weighing fluorinated graphene and sodium amide in a mass ratio of 1:1; adding fluorinated graphene to diphenyl ether for ultrasonic dispersion, adding sodium amide, introducing nitrogen, reacting at 162° C. for 12 hours, cooling to room temperature, quenching with methanol, purifying, and drying to obtain amino fluorinated graphene; (2) adding chopped quartz fibers to a 0.024 wt% H 2 SO 4 The aqueous solution was stirred and ultrasonically treated for 5 minutes, placed at 65°C for reaction for 55 minutes, cooled to room temperature, and amino-fluorinated graphene was added, stirred for 1.2 hours, the pH was adjusted to neutral, washed, and dried to obtain a modified composite material; the amino-fluorinated graphene accounted for 0.35wt% of the chopped quartz fiber;

[0025] S4: 65 parts of polyetheretherketone, 25 parts of modified polyetheretherketone, 3 parts of modified fluorinated graphene, and 15 parts of modified composite materials are uniformly mixed to obtain a premix; the premix is ​​placed in a twin-screw extruder for melt extrusion, and the process conditions are: the temperature of zone one is 330°C, the temperature of zone two is 350°C, the temperature of zone three is 355°C, the temperature of zone four is 360°C, the temperature of zone five is 365°C, the temperature of zone six is ​​370°C, the temperature of zone seven is 375°C, the temperature of zone eight is 375°C, the temperature of zone nine is 375°C, the temperature of zone ten is 370°C, the temperature of zone eleven is 370°C, the temperature of the machine head is 378°C, the main engine speed is 400r / min, and the wire is drawn and wound to obtain a 1.7mm 3D printing wire.

[0026] Embodiment 2:

[0027] S1: (1) Under nitrogen protection, 8 parts of 4,4'-diaminodiphenyl ether are dissolved in 100 parts of N,N-dimethylacetamide and stirred for 5 minutes, 18 parts of biphenyl diether dianhydride are added and reacted at room temperature for 13 hours, 2.5 parts of phenylacetylene tricarboxylic anhydride are added and the reaction is continued for 6 hours, 13 parts of triethylamine and 13 parts of acetic anhydride are added in sequence, the reaction is continued for 4 hours, ethanol is washed 3 times, and dried to obtain polyetherimide; (2) polyetherimide and polyetheretherketone are mixed uniformly, placed in a single screw extruder for melt extrusion granulation, and the process conditions are: zone 1 temperature is 325°C, zone 2 temperature is 350°C, zone 3 temperature is 365°C, die head temperature is 360°C, and rotation speed is 30r / min; modified polyetheretherketone is obtained; wherein the polyetherimide accounts for 18wt% of the polyetheretherketone;

[0028] S2: (1) Weighing fluorinated graphene and N-methyl-2-pyrrolidone in a mass ratio of 0.01:1.2; adding fluorinated graphene to N-methyl-2-pyrrolidone, reacting at 65°C for 4.5 hours, cooling to room temperature, ultrasonically treating in an ice bath for 14 hours, centrifuging, and washing the precipitate with ethanol four times to obtain perfluorinated graphene; (2) adding 1.2 parts of perfluorinated graphene, 0.65 parts of bisphenol A and 1 part of potassium carbonate to a mixed solution of 8 parts of cyclopentane sulfone and 2 parts of toluene, stirring at 142°C for 1.2 hours under nitrogen protection, heating to 175°C for 2 hours, cooling to room temperature, centrifuging, and washing the precipitate with ethanol four times to obtain modified fluorinated graphene;

[0029] S3: (1) weighing fluorinated graphene and sodium amide in a mass ratio of 1:2; adding fluorinated graphene to diphenyl ether for ultrasonic dispersion, adding sodium amide, introducing nitrogen, reacting at 162° C. for 12 hours, cooling to room temperature, quenching with methanol, purifying, and drying to obtain amino fluorinated graphene; (2) adding chopped quartz fibers to a 0.024 wt% H 2 SO 4 The aqueous solution was stirred and ultrasonically treated for 5 minutes, placed at 65°C for reaction for 55 minutes, cooled to room temperature, and amino-fluorinated graphene was added, stirred for 1.2 hours, the pH was adjusted to neutral, washed, and dried to obtain a modified composite material; the amino-fluorinated graphene accounted for 0.35wt% of the chopped quartz fiber;

[0030] S4: 62 parts of polyetheretherketone, 34 parts of modified polyetheretherketone, 4.5 parts of modified fluorinated graphene, and 18 parts of modified composite materials are uniformly mixed to obtain a premix; the premix is ​​placed in a twin-screw extruder for melt extrusion, and the process conditions are: the temperature of zone one is 330°C, the temperature of zone two is 350°C, the temperature of zone three is 355°C, the temperature of zone four is 360°C, the temperature of zone five is 365°C, the temperature of zone six is ​​370°C, the temperature of zone seven is 375°C, the temperature of zone eight is 375°C, the temperature of zone nine is 375°C, the temperature of zone ten is 370°C, the temperature of zone eleven is 370°C, the temperature of the machine head is 378°C, the main engine speed is 400r / min, and the wire is drawn and wound to obtain a 1.7mm 3D printing wire.

[0031] Embodiment 3:

[0032] S1: (1) Under nitrogen protection, 8 parts of 4,4'-diaminodiphenyl ether are dissolved in 100 parts of N,N-dimethylacetamide and stirred for 5 minutes, 20 parts of biphenyl diether dianhydride are added and reacted at room temperature for 13 hours, 3 parts of phenylacetylene tricarboxylic anhydride are added and the reaction is continued for 6 hours, 13 parts of triethylamine and 12 parts of acetic anhydride are added in sequence and reacted for 4 hours, ethanol is washed 3 times, and dried to obtain polyetherimide; (2) polyetherimide and polyetheretherketone are mixed uniformly, placed in a single screw extruder for melt extrusion granulation, and the process conditions are: zone 1 temperature is 325°C, zone 2 temperature is 350°C, zone 3 temperature is 365°C, die head temperature is 360°C, and rotation speed is 30r / min; modified polyetheretherketone is obtained; wherein the polyetherimide accounts for 18wt% of the polyetheretherketone;

[0033] S2: (1) Weighing fluorinated graphene and N-methyl-2-pyrrolidone in a mass ratio of 0.01:1; adding fluorinated graphene to N-methyl-2-pyrrolidone, reacting at 65°C for 4.5 hours, cooling to room temperature, ultrasonically treating in an ice bath for 14 hours, centrifuging, and washing the precipitate with ethanol four times to obtain perfluorinated graphene; (2) adding 1.2 parts of perfluorinated graphene, 1 part of bisphenol fluorene, and 1 part of potassium carbonate to a mixed solution of 8 parts of cyclopentane sulfone and 2 parts of toluene, stirring at 142°C for 2 hours under nitrogen protection, heating to 175°C for 2 hours, cooling to room temperature, centrifuging, and washing the precipitate with ethanol four times to obtain modified fluorinated graphene;

[0034] S3: (1) weighing fluorinated graphene and sodium amide in a mass ratio of 1:2; adding fluorinated graphene to diphenyl ether for ultrasonic dispersion, adding sodium amide, introducing nitrogen, reacting at 162° C. for 12 hours, cooling to room temperature, quenching with methanol, purifying, and drying to obtain amino fluorinated graphene; (2) adding chopped quartz fibers to a 0.024 wt% H 2 SO 4 The aqueous solution was stirred and ultrasonically treated for 5 minutes, placed at 65°C for reaction for 55 minutes, cooled to room temperature, and amino-fluorinated graphene was added, stirred for 1.2 hours, the pH was adjusted to neutral, washed, and dried to obtain a modified composite material; the amino-fluorinated graphene accounted for 0.4wt% of the chopped quartz fiber;

[0035] S4: 70 parts of polyetheretherketone, 25 parts of modified polyetheretherketone, 5 parts of modified fluorinated graphene, and 15 parts of modified composite materials are uniformly mixed to obtain a premix; the premix is ​​placed in a twin-screw extruder for melt extrude, and the process conditions are: the temperature of zone one is 330°C, the temperature of zone two is 350°C, the temperature of zone three is 355°C, the temperature of zone four is 360°C, the temperature of zone five is 365°C, the temperature of zone six is ​​370°C, the temperature of zone seven is 375°C, the temperature of zone eight is 375°C, the temperature of zone nine is 375°C, the temperature of zone ten is 370°C, the temperature of zone eleven is 370°C, the temperature of the machine head is 378°C, the main engine speed is 400r / min, and the wire is drawn and wound to obtain a 1.7mm 3D printing wire.

[0036] Comparative Example 1 is based on Example 2, but without adding modified polyetheretherketone;

[0037] S1: (1) Weighing fluorinated graphene and N-methyl-2-pyrrolidone in a mass ratio of 0.01:1.2; adding fluorinated graphene to N-methyl-2-pyrrolidone, reacting at 65°C for 4.5 hours, cooling to room temperature, ultrasonically treating in an ice bath for 14 hours, centrifuging, and washing the precipitate with ethanol for 4 times to obtain perfluorinated graphene; (2) adding 1.2 parts of perfluorinated graphene, 0.65 parts of bisphenol A and 1 part of potassium carbonate to a mixed solution of 8 parts of cyclopentane sulfone and 2 parts of toluene, stirring at 142°C for 1.2 hours under nitrogen protection, heating to 175°C for 2 hours, cooling to room temperature, centrifuging, and washing the precipitate with ethanol for 4 times to obtain modified fluorinated graphene;

[0038] S2: (1) weighing fluorinated graphene and sodium amide in a mass ratio of 1:2; adding fluorinated graphene to diphenyl ether for ultrasonic dispersion, adding sodium amide, introducing nitrogen, reacting at 162° C. for 12 hours, cooling to room temperature, quenching with methanol, purifying, and drying to obtain amino fluorinated graphene; (2) adding chopped quartz fibers to a 0.024wt% H 2 SO 4 The aqueous solution was stirred and ultrasonically treated for 5 minutes, placed at 65°C for reaction for 55 minutes, cooled to room temperature, and amino-fluorinated graphene was added, stirred for 1.2 hours, the pH was adjusted to neutral, washed, and dried to obtain a modified composite material; the amino-fluorinated graphene accounted for 0.35wt% of the chopped quartz fiber;

[0039] S3: 62 parts of polyetheretherketone, 4.5 parts of modified fluorinated graphene and 18 parts of modified composite materials are uniformly mixed to obtain a premix; the premix is ​​placed in a twin-screw extruder for melt extrusion, and the process conditions are: the temperature of zone 1 is 330°C, the temperature of zone 2 is 350°C, the temperature of zone 3 is 355°C, the temperature of zone 4 is 360°C, the temperature of zone 5 is 365°C, the temperature of zone 6 is 370°C, the temperature of zone 7 is 375°C, the temperature of zone 8 is 375°C, the temperature of zone 9 is 375°C, the temperature of zone 10 is 370°C, the temperature of zone 11 is 370°C, the temperature of the machine head is 378°C, the main engine speed is 400r / min, and the wire is drawn and wound to obtain a 1.7mm 3D printing wire.

[0040] Comparative Example 2 is based on Example 2, except that the modified fluorinated graphene is not replaced with perfluorinated graphene;

[0041] S1: (1) Under nitrogen protection, 8 parts of 4,4'-diaminodiphenyl ether are dissolved in 100 parts of N,N-dimethylacetamide and stirred for 5 minutes, 18 parts of biphenyl diether dianhydride are added and reacted at room temperature for 13 hours, 2.5 parts of phenylacetylene tricarboxylic anhydride are added and the reaction is continued for 6 hours, 13 parts of triethylamine and 13 parts of acetic anhydride are added in sequence, the reaction is continued for 4 hours, ethanol is washed 3 times, and dried to obtain polyetherimide; (2) polyetherimide and polyetheretherketone are mixed uniformly, placed in a single screw extruder for melt extrusion granulation, and the process conditions are: zone 1 temperature is 325°C, zone 2 temperature is 350°C, zone 3 temperature is 365°C, die head temperature is 360°C, and rotation speed is 30r / min; modified polyetheretherketone is obtained; wherein the polyetherimide accounts for 18wt% of the polyetheretherketone;

[0042] S2: Weighing fluorinated graphene and N-methyl-2-pyrrolidone in a mass ratio of 0.01:1.2; adding fluorinated graphene to N-methyl-2-pyrrolidone, reacting at 65° C. for 4.5 hours, cooling to room temperature, ultrasonically treating in an ice bath for 14 hours, centrifuging, and washing the precipitate with ethanol for 4 times to obtain perfluorinated graphene;

[0043] S3: (1) weighing fluorinated graphene and sodium amide in a mass ratio of 1:2; adding fluorinated graphene to diphenyl ether for ultrasonic dispersion, adding sodium amide, introducing nitrogen, reacting at 162° C. for 12 hours, cooling to room temperature, quenching with methanol, purifying, and drying to obtain amino fluorinated graphene; (2) adding chopped quartz fibers to a 0.024 wt% H 2 SO 4 The aqueous solution was stirred and ultrasonically treated for 5 minutes, placed at 65°C for reaction for 55 minutes, cooled to room temperature, and amino-fluorinated graphene was added, stirred for 1.2 hours, the pH was adjusted to neutral, washed, and dried to obtain a modified composite material; the amino-fluorinated graphene accounted for 0.35wt% of the chopped quartz fiber;

[0044] S4: 62 parts of polyetheretherketone, 34 parts of modified polyetheretherketone, 4.5 parts of perfluorinated graphene, and 18 parts of modified composite materials are uniformly mixed to obtain a premix; the premix is ​​placed in a twin-screw extruder for melt extrusion, and the process conditions are: the temperature of zone one is 330°C, the temperature of zone two is 350°C, the temperature of zone three is 355°C, the temperature of zone four is 360°C, the temperature of zone five is 365°C, the temperature of zone six is ​​370°C, the temperature of zone seven is 375°C, the temperature of zone eight is 375°C, the temperature of zone nine is 375°C, the temperature of zone ten is 370°C, the temperature of zone eleven is 370°C, the temperature of the machine head is 378°C, the main engine speed is 400r / min, and the wire is drawn and wound to obtain a 1.7mm 3D printing wire.

[0045] Comparative Example 3 is based on Example 2, but without adding amino-fluorinated graphene;

[0046] S1: (1) Under nitrogen protection, 8 parts of 4,4'-diaminodiphenyl ether are dissolved in 100 parts of N,N-dimethylacetamide and stirred for 5 minutes, 18 parts of biphenyl diether dianhydride are added and reacted at room temperature for 13 hours, 2.5 parts of phenylacetylene tricarboxylic anhydride are added and the reaction is continued for 6 hours, 13 parts of triethylamine and 13 parts of acetic anhydride are added in sequence, the reaction is continued for 4 hours, ethanol is washed 3 times, and dried to obtain polyetherimide; (2) polyetherimide and polyetheretherketone are mixed uniformly, placed in a single screw extruder for melt extrusion granulation, and the process conditions are: zone 1 temperature is 325°C, zone 2 temperature is 350°C, zone 3 temperature is 365°C, die head temperature is 360°C, and rotation speed is 30r / min; modified polyetheretherketone is obtained; wherein the polyetherimide accounts for 18wt% of the polyetheretherketone;

[0047] S2: (1) Weighing fluorinated graphene and N-methyl-2-pyrrolidone in a mass ratio of 0.01:1.2; adding fluorinated graphene to N-methyl-2-pyrrolidone, reacting at 65°C for 4.5 hours, cooling to room temperature, ultrasonically treating in an ice bath for 14 hours, centrifuging, and washing the precipitate with ethanol four times to obtain perfluorinated graphene; (2) adding 1.2 parts of perfluorinated graphene, 0.65 parts of bisphenol A and 1 part of potassium carbonate to a mixed solution of 8 parts of cyclopentane sulfone and 2 parts of toluene, stirring at 142°C for 1.2 hours under nitrogen protection, heating to 175°C for 2 hours, cooling to room temperature, centrifuging, and washing the precipitate with ethanol four times to obtain modified fluorinated graphene;

[0048] S3: (2) Add chopped quartz fibers into a 0.024 wt% H 2 SO 4 The aqueous solution was stirred and ultrasonically treated for 5 minutes, placed at 65°C for reaction for 55 minutes, cooled to room temperature, and amino-fluorinated graphene was added, stirred for 1.2 hours, the pH was adjusted to neutral, washed, and dried to obtain modified quartz fibers;

[0049] S4: 62 parts of polyetheretherketone, 34 parts of modified polyetheretherketone, 4.5 parts of modified fluorinated graphene, and 18 parts of modified quartz fiber are uniformly mixed to obtain a premix; the premix is ​​placed in a twin-screw extruder for melt extrusion, and the process conditions are: the temperature of zone one is 330°C, the temperature of zone two is 350°C, the temperature of zone three is 355°C, the temperature of zone four is 360°C, the temperature of zone five is 365°C, the temperature of zone six is ​​370°C, the temperature of zone seven is 375°C, the temperature of zone eight is 375°C, the temperature of zone nine is 375°C, the temperature of zone ten is 370°C, the temperature of zone eleven is 370°C, the temperature of the machine head is 378°C, the main engine speed is 400r / min, and the wire is drawn and wound to obtain a 1.7mm 3D printing wire.

[0050] Comparative Example 4 is based on Example 2, except that the twin-screw extrusion is replaced with a single-screw extrusion;

[0051] S1: (1) Under nitrogen protection, 8 parts of 4,4'-diaminodiphenyl ether are dissolved in 100 parts of N,N-dimethylacetamide and stirred for 5 minutes, 18 parts of biphenyl diether dianhydride are added and reacted at room temperature for 13 hours, 2.5 parts of phenylacetylene tricarboxylic anhydride are added and the reaction is continued for 6 hours, 13 parts of triethylamine and 13 parts of acetic anhydride are added in sequence, the reaction is continued for 4 hours, ethanol is washed 3 times, and dried to obtain polyetherimide; (2) polyetherimide and polyetheretherketone are mixed uniformly, placed in a single screw extruder for melt extrusion granulation, and the process conditions are: zone 1 temperature is 325°C, zone 2 temperature is 350°C, zone 3 temperature is 365°C, die head temperature is 360°C, and rotation speed is 30r / min; modified polyetheretherketone is obtained; wherein the polyetherimide accounts for 18wt% of the polyetheretherketone;

[0052] S2: (1) Weighing fluorinated graphene and N-methyl-2-pyrrolidone in a mass ratio of 0.01:1.2; adding fluorinated graphene to N-methyl-2-pyrrolidone, reacting at 65°C for 4.5 hours, cooling to room temperature, ultrasonically treating in an ice bath for 14 hours, centrifuging, and washing the precipitate with ethanol four times to obtain perfluorinated graphene; (2) adding 1.2 parts of perfluorinated graphene, 0.65 parts of bisphenol A and 1 part of potassium carbonate to a mixed solution of 8 parts of cyclopentane sulfone and 2 parts of toluene, stirring at 142°C for 1.2 hours under nitrogen protection, heating to 175°C for 2 hours, cooling to room temperature, centrifuging, and washing the precipitate with ethanol four times to obtain modified fluorinated graphene;

[0053] S3: (1) weighing fluorinated graphene and sodium amide in a mass ratio of 1:2; adding fluorinated graphene to diphenyl ether for ultrasonic dispersion, adding sodium amide, introducing nitrogen, reacting at 162° C. for 12 hours, cooling to room temperature, quenching with methanol, purifying, and drying to obtain amino fluorinated graphene; (2) adding chopped quartz fibers to a 0.024 wt% H 2 SO 4The aqueous solution was stirred and ultrasonically treated for 5 minutes, placed at 65°C for reaction for 55 minutes, cooled to room temperature, and amino-fluorinated graphene was added, stirred for 1.2 hours, the pH was adjusted to neutral, washed, and dried to obtain a modified composite material; the amino-fluorinated graphene accounted for 0.35wt% of the chopped quartz fiber;

[0054] S4: 62 parts of polyetheretherketone, 34 parts of modified polyetheretherketone, 4.5 parts of modified fluorinated graphene and 18 parts of modified composite materials are uniformly mixed to obtain a premix; the premix is ​​placed in a single screw extruder for melt extrusion, and the process conditions are: the temperature of zone 1 is 325°C, the temperature of zone 2 is 350°C, the temperature of zone 3 is 365°C, the temperature of die head is 360°C, the rotation speed is 30r / min, and the wire is drawn and wound to obtain a 1.7mm 3D printing wire.

[0055] Test experiment 1: Salt spray test: For the samples of Examples 1 to 3 and Comparative Examples 1 to 4, 6 specimens were taken in each group, and the specimens were placed in a test box in multiple batches and treated for 96 hours under the same test conditions. The temperature of the test box was 35°C, the salt concentration was 5wt%, the pH value was 6.8, and the relative humidity of the air was 90%; the tensile strength of Examples 1 to 3 and Comparative Examples 1 to 4 before and after the salt spray test was obtained according to ASTM D4018-11, and the tensile strength decrease rate (%) was calculated.

[0056] Tensile strength(MPa) Tensile strength decrease rate (%) Example 1 202.5 1.82% Example 2 210.7 1.74% Example 3 198.9 1.94% Comparative Example 1 169.7 4.85% Comparative Example 2 185.9 2.47% Comparative Example 3 177.9 3.45% Comparative Example 4 192.7 2.18%

[0057] Table 1

[0058] Conclusion: Comparative Example 1 is based on Example 2, and modified polyetheretherketone is not added, thereby reducing the strength and corrosion resistance of Comparative Example 1. Modified polyetheretherketone is obtained by cross-linking with polyetheretherketone after introducing cross-linking groups into polyetherimide, and polyetherimide itself has good strength and rigidity, which is beneficial to enhance the stability and strength of 3D printing wire. Comparative Example 2 is based on Example 2, and the modified fluorinated graphene is not replaced with perfluorinated graphene. Although it can improve the corrosion resistance of 3D printing wire, the introduction of fluorene groups can improve the dispersibility of perfluorinated graphene in the material, and the fluorene groups have rigidity, which can improve the strength of 3D printing wire. Comparative Example 3 is based on Example 2, and amino fluorinated graphene is not added, thereby reducing the corrosion resistance and strength of 3D printing wire. Because fluorinated graphene has good strength and corrosion resistance, after introducing amino groups, it forms a covalent connection with hydroxylated chopped quartz fibers, which helps to enhance the strength and corrosion resistance of 3D printing wire. Comparative Example 4 is based on Example 2, and the twin-screw extrusion is replaced with a single-screw extrusion, thereby reducing the strength and corrosion resistance of the 3D printing wire. Because the twin-screw is set to extrude in different temperature zones, and has a more complex screw configuration that is conducive to mixing, the dispersibility and fluidity of the modified material can be improved, and the additives can be fully dispersed in the matrix, thereby improving the performance of the 3D printing wire.

[0059] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.

Claims

1. A method for preparing a high-strength, corrosion-resistant special 3D printing wire, characterized in that: The steps include: S1: preparing modified fluorinated graphene: (1) reacting fluorinated graphene with N-methyl-2-pyrrolidone to obtain perfluorinated graphene; (2) reacting perfluorinated graphene with bisphenol fluorene using potassium carbonate as a catalyst to obtain modified fluorinated graphene; S2: uniformly mixing polyetheretherketone, modified polyetheretherketone, modified fluorinated graphene and modified composite material to obtain a premix, melt-extrude the premix, and draw and wind the premix to obtain a 3D printing filament.

2. The method for preparing a high-strength, corrosion-resistant special 3D printing wire according to claim 1, characterized in that: The raw materials of the premix include the following components: by weight, 62 to 75 parts of polyetheretherketone, 25 to 35 parts of modified polyetheretherketone, 3 to 5 parts of modified fluorinated graphene, and 15 to 20 parts of modified composite material.

3. The method for preparing a high-strength, corrosion-resistant special 3D printing wire according to claim 1, characterized in that: The preparation method of modified fluorinated graphene is as follows: (1) adding fluorinated graphene to N-methyl-2-pyrrolidone, reacting at 55-65° C. for 4.5-7 hours, cooling to room temperature, ultrasonically treating in an ice bath for 14-16 hours, purifying, and obtaining perfluorinated graphene; (2) adding perfluorinated graphene, bisphenol fluorene, and potassium carbonate to a mixed solution of cyclopentane sulfone and toluene, stirring at 135-145° C. for 1-2 hours under nitrogen protection, heating to 160-175° C. for reaction for 1.5-2.5 hours, cooling to room temperature, purifying, and drying to obtain modified fluorinated graphene.

4. The method for preparing a high-strength, corrosion-resistant special 3D printing wire according to claim 3, characterized in that: The mass ratio of fluorinated graphene to N-methyl-2-pyrrolidone is (0.005-0.01):1; the raw materials of modified fluorinated graphene include the following components: by weight, 1-1.5 parts of perfluorinated graphene, 0.2-0.8 parts of bisphenol fluorene, 0.8-1.2 parts of potassium carbonate, 8-10 parts of cyclopentane sulfone, and 2-3 parts of toluene.

5. The method for preparing a high-strength, corrosion-resistant special 3D printing wire according to claim 1, characterized in that: The preparation method of the modified composite material is as follows: (1) adding fluorinated graphene to diphenyl ether for ultrasonic dispersion, adding sodium amide, introducing nitrogen, reacting at 160-165° C. for 12-13 hours, cooling to room temperature, quenching, purifying, and obtaining amino fluorinated graphene; (2) placing short quartz fibers in H2SO4 aqueous solution, stirring and ultrasonically treating for 5-7 minutes, placing at 55-65° C. for reaction for 45-65 minutes, cooling to room temperature, adding amino fluorinated graphene, stirring for 1-1.2 hours, adjusting the pH to neutral, washing, and drying to obtain the modified composite material.

6. The method for preparing a high-strength, corrosion-resistant special 3D printing wire according to claim 5, characterized in that: The concentration of the H2SO4 aqueous solution is 0.023-0.037wt%; the mass ratio of sodium amide to fluorinated graphene is (1-2):1; the aminated fluorinated graphene accounts for 0.2-0.4wt% of the chopped quartz fibers.

7. The method for preparing a high-strength, corrosion-resistant special 3D printing wire according to claim 1, characterized in that: The preparation method of the modified polyetheretherketone is as follows: (1) under nitrogen protection, dissolving 4,4'-diaminodiphenyl ether in N,N-dimethylacetamide and stirring for 5 to 10 minutes, adding diphenyl diether dianhydride and reacting at room temperature for 12 to 14 hours, adding phenylacetylene tricarboxylic anhydride and continuing the reaction for 5 to 6.5 hours, adding triethylamine and acetic anhydride in sequence, reacting for 3 to 4 hours, purifying, and obtaining polyetherimide; (2) mixing polyetherimide and polyetheretherketone uniformly, and melt-extruding and granulating to obtain modified polyetheretherketone.

8. The method for preparing a high-strength, corrosion-resistant special 3D printing wire according to claim 7, characterized in that: The raw materials of polyetherimide include the following components: 8-10 parts of 4,4'-diaminodiphenyl ether, 18-22 parts of biphenyl diether dianhydride, 2-3 parts of phenylacetylene tricarboxylic anhydride, 12-14 parts of triethylamine, 12-14 parts of acetic anhydride, and 100-200 parts of N,N-dimethylacetamide, by weight; the polyetherimide accounts for 16-20wt% of the polyetheretherketone; the process conditions of melt extrusion granulation are: the temperature of the first zone is 320-325℃, the temperature of the second zone is 345-350℃, the temperature of the third zone is 362-365℃, the temperature of the die head is 360℃, and the rotation speed is 27-35r / min.

9. The method for preparing a high-strength, corrosion-resistant special 3D printing wire according to claim 1, characterized in that: The process conditions of melt extrusion are: temperature of zone 1 is 325-335°C, temperature of zones 2 to 11 is 350-375°C, temperature of die head is 378°C, and main engine speed is 350-450r / min.

10. A 3D printing wire is prepared according to the method for preparing a high-strength, corrosion-resistant special 3D printing wire according to any one of claims 1 to 9.

Citation Information

Cited By

  • Corrosion-resistant PE plate and preparation method thereof

    CN120441951A